BS41 Enhancing cardiac regeneration: the role of fibronectin in stem cell-derived epicardial-cardiomyocyte crosstalk. (6th June 2022) - Lee, Jonathan Chuo Min; Ong, Lay Ping; Bayraktar, Semih; Rericha, Patrick; Knight-Schrijver, Vincent; Colzani, Maria; Bargehr, Johannes; Gambardella, Laure; Sinha, Sanjay
Abstract : Background: Heart failure remains to be one of the major causes of morbidity and mortality post-myocardial infarction. Current therapeutic strategies are aimed at minimising progression, but apart from cardiac transplantation, no treatment thus far has addressed the loss of contractile tissue post-injury. Transplantation of human embryonic stem cell-derived cardiomyocytes (hESC-CMs) has emerged as a promising strategy to address this issue, but these treatments remain inefficient. hESC- epicardium (hESC-Epis) has been shown to improve the function of hESC-CMs in vitro and post-transplantation into animal myocardial infarction models. However, the underlying mechanisms mediating these effects remain poorly characterised. Bulk RNA sequencing of hESC-Epis suggests a role for genes related to extracellular matrix remodelling in mediating these effects, with fibronectin (FN1) being highly implicated. Study Objective To examine the role of FN1 in hESC-CM/Epi crosstalk through gain and loss of function studies. Methods: A tetracycline inducible FN1 knockdown system was used on both hESC-CMs and Epis within the setting of3D-engineered heart tissue. Changes in contractility, Frank-Starling behaviour and calcium handling were measured as functional endpoints. Gain of function studies were then performed using recombinant human plasma FN1 (rhFN) to determine the effect of FN1 supplementation on hESC-CM function and maturity. Results: FN1 knockdown in hESC-Epis resulted in significant abrogation of the beneficial effects on hESC-CM force generation and calcium handling. Knockdown of FN1 in hESC-CMs however significantly attenuated contractility of the hESC-CMs but had no effects on calcium handling. When rhFN was added to hESC-CMs in increasing doses, hESC-CM contractility was improved in a dose dependent fashion to the same extent as seen with hESC-Epis co-cultures. However, no significant improvement was observed in calcium handling regardless of dosing. Conclusions: hESC-CM and Epi crosstalk improving hESC-CM function may rely heavily on the presence of FN1. FN1 secreted by both cell types are shown to be of importance in this crosstalk with artificial supplementation of rhFN being able to recapitulate some beneficial effects of hESC-Epis on hESC-CMs. Further studies are required to determine the role of specific isoforms of secreted FN1 on hESC-CM maturity and to identify the underlying mechanisms which mediate these effects. This opens up the possibility of improving cell-based therapy for heart failure post-myocardial infarction using recombinant FN1 supplementation.